PENGARUH INTELLECTUAL CAPITAL, ACCRUAL COMPONENT, DAN FAKTOR LAINNYA TERHADAP FINANCIAL DISTRESS - Ath-Thahir, Lamya Varany; Wijaya, Novia (E-Jurnal Akuntansi TSM, 2023)
Financial distress is a condition where a company experiences a continuous decline in finances which can lead to bankruptcy, therefore financial distress is an important thing. The aim of this research is to obtain empirical evidence about the influence of intellectual capital, accrual components and other factors on financial distress in companies in the consumer cyclical and non-cyclical sectors listed on the Indonesia Stock Exchange (BEI). The variables used in this research are leverage, working capital, company size, cash flow from operations, profitability, sales growth, accrual components, and intellectual capital. 378 data from 2020-2022 were obtained using the purposive sampling method. Data were analyzed using the multiple regression method. The results show that all independent variables, namely leverage, working capital, company size, cash flow from operations, profitability, sales growth, accrual components and intellectual capital have no influence on financial distress.